Dermatose por IgA linear induzida pela gestação Linear IgA dermatosis induced by pregnancy - Telma Kanagusuko; Valéria Aoki; Antonio José Tebcherani; Ana Paula Galli Sanchez (Anais Brasileiros de Dermatologia, 2008)
A dermatose por IgA linear é doença bolhosa auto-imune subepidérmica rara, caracterizada pelo depósito linear de IgA na zona da membrana basal da epiderme. Nos relatos de gestação em pacientes com essa dermatose, nota-se sempre melhora do quadro clínico. Contrariando essas observações,é apresentado caso de dermatose por IgA linear induzida pela gestação, que demonstrou boa resposta terapêutica à dapsona e prednisona , sem complicações materno-fetais. Linear IgA disease is a rare autoimmune subepidermal bullous disorder characterized by linear IgA deposits at the epidermal basement membrane zone. According to the literature, in patients who have linear IgA disease and become pregnant, the disease tends to improve. We report a case of linear IgA disease induced by pregnancy, successfully treated with dapsone and prednisone with no adverse effects observed in the patient and her newborns.